Peranan Administrasi Negara Dalam Kehidupan Berbangsa dan Bernegara Dalam Sudut Pandang Islam - Rahmawati Rahmawati (Jurnal Pemerintahan dan Politik, 2019)
Abstract In the times at the moment where people are growing increasingly progressing to become an advanced society and modern, and in any social development is closely linked to the changes that occurred in the midst of society, especially in the decisions and policies set by the State Administration. This is because the community is part of a large organization called the state, so that the life of the nation cannot be separated from the interference of the state in regulating the public interest. One form of government participation in managing public interests is the Public Administration (State). Administration is not limited to the activities of writing, but covers a wider field. Administration was not a familiar thing in everyday life. In addition, we also often find him anywhere and anytime in the aspects of our lives. However, many people do not know and understand the meaning and significance of what is true about the administration Administration is not new that exist in modern times, but it has existed since time immemorial. The basics of the administration is in the time is now there at the time of the Prophet first. As the distribution of zakat, inheritance, registration of accounts payable, the distribution of alms to the people around who are less able, it is already included in the activities of the administration. The sources are contained in the Qur'an, the Sunnah and Hadist. Islam has the concept of the state administration and administration of comprehensive government as exemplified by the Prophet for leading the community in Medina. In Islam the state institutions cannot be separated from the collective concept that exists in a moral foundation and Islamic law. Keywords: Role of the State Administration in the Life of Nation and State in Islam Perspecti Abstrak Pada saat-saat di saat orang-orang tumbuh semakin maju untuk menjadi masyarakat yang maju dan modern, dan dalam setiap perkembangan sosial sangat terkait dengan perubahan yang terjadi di tengah-tengah masyarakat, terutama dalam keputusan dan kebijakan yang ditetapkan oleh Administrasi Negara . Ini karena masyarakat adalah bagian dari organisasi besar yang disebut negara, sehingga kehidupan berbangsa tidak dapat dipisahkan dari campur tangan negara dalam mengatur kepentingan publik. Salah satu bentuk partisipasi pemerintah dalam mengelola kepentingan publik adalah Administrasi Publik (Negara). Administrasi tidak terbatas pada kegiatan menulis, tetapi mencakup bidang yang lebih luas. Administrasi bukanlah hal yang lazim dalam kehidupan sehari-hari. Selain itu, kita juga sering menemukannya di mana saja dan kapan saja dalam aspek kehidupan kita. Namun, banyak orang tidak tahu dan mengerti arti dan arti dari apa yang benar tentang administrasi administrasi bukanlah hal baru yang ada di zaman modern, tetapi sudah ada sejak dahulu kala. Dasar-dasar administrasi adalah pada waktunya sekarang ada pada zaman Nabi pertama. Sebagai distribusi zakat, pewarisan, pendaftaran hutang, distribusi sedekah kepada orang-orang sekitar yang kurang mampu, itu sudah termasuk dalam kegiatan administrasi. Sumber-sumbernya terkandung dalam Al Qur'an, Sunnah dan Hadist. Islam memiliki konsep administrasi negara dan administrasi pemerintahan yang komprehensif sebagaimana dicontohkan oleh Nabi untuk memimpin masyarakat di Madinah. Dalam Islam, institusi negara tidak dapat dipisahkan dari konsep kolektif yang ada dalam landasan moral dan hukum Islam. Kata Kunci: Peran Administrasi Negara dalam Kehidupan Bangsa dan Negara dalam Perspektif Islam